Ambulatory management of secondary spontaneous pneumothorax: a mirage, or a solution on the horizon?. Issue 6 (24th June 2021) - Mummadi, Srinivas R.; Porcel, José M.
Secondary spontaneous pneumothorax (SSP) exemplifies the idea of a "wicked problem" [1]: the type of challenge with complicated solutions that must be examined carefully, in order to avoid compounding the problem itself. In this case, the problem, SSP, is characterised by an equally problematic immediate solution, namely prolonged hospitalisation. As extended hospital stays are costly to SSP patients and healthcare systems alike, ambulatory management might appear to be an appealing alternative. Recent randomised trials and prior observational studies have demonstrated the efficacy of ambulatory management in primary spontaneous pneumothorax (PSP) [2–7] and iatrogenic pneumothorax [8]. While PSP and SSP are thought of as distinct clinical syndromes, recent radiological and pathological data [9, 10] challenge this assumption. PSP and SSP are likely at different ends of the spontaneous pneumothorax spectrum. Ambulatory management of selected patients with secondary spontaneous pneumothorax using small-bore chest catheters (12F) with an attached one-way flutter valve device seems feasible and safe https://bit.ly/3oycMpG